On a new genus of the fossorial wolf spiders from Middle Asia (Araneae, Lycosidae) - Logunov, Dmitry V.; Nekhaeva, Anna A. (Zootaxa, 2026)
A new genus, Desertosa gen. nov., is established to accommodate six Middle Asian species of burrowing wolf spiders, of which four are diagnosed and described as new: D. karamola sp. nov. (male, female, SE Kazakhstan), D. kuramin sp. nov. (female, SE Uzbekistan), D. ozernoyi sp. nov. (male, female, SE Kazakhstan), D. zyuzini sp. nov. (male, female, SE Kazakhstan). Two new combinations are proposed: Desertosa kuryk (Esyunin & Efimik, 2025), comb. nov. and D. uzbekistanica (Logunov, 2023), comb. nov.; both ex Lycosa Latreille, 1804. The localities of all Desertosa species are mapped, and an identification key is provided as well. A brief synopsis of the fauna and diversity of the fossorial Lycosidae of Middles Asia is given.